Human subtelomeric WASH genes encode a new subclass of the WASP family. - Elena V Linardopoulou; Sean S Parghi; Cynthia Friedman; Gregory E Osborn; Susan M Parkhurst; Barbara J Trask (PLoS Genetics)
Subtelomeres are duplication-rich, structurally variable regions of the human genome situated just proximal of telomeres. We report here that the most terminally located human subtelomeric genes encode a previously unrecognized third subclass of the Wiskott-Aldrich Syndrome Protein family, whose known members reorganize the actin cytoskeleton in response to extracellular stimuli. This new subclass, which we call WASH, is evolutionarily conserved in species as diverged as Entamoeba. We demonstrate that WASH is essential in Drosophila. WASH is widely expressed in human tissues, and human WASH protein colocalizes with actin in filopodia and lamellipodia. The VCA domain of human WASH promotes actin polymerization by the Arp2/3 complex in vitro. WASH duplicated to multiple chromosomal ends during primate evolution, with highest copy number reached in humans, whose WASH repertoires vary. Thus, human subtelomeres are not genetic junkyards, and WASH's location in these dynamic regions could have advantageous as well as pathologic consequences.